Unmixing behaviour in dissimilar laser welds for duplex and austenitic stainless steels. (3rd April 2019) - Chun, Eun-Joon; Lee, Jung-Hoon; Kang, Namhyun
ABSTRACT: Metallurgical characteristics of single-mode laser dissimilar welds between super duplex (UNS S32750) and austenitic (type 316L) stainless steels is the existence of an unmixed zone that originates from each base metal. It was confirmed that the unmixed zone that flowed out from the 316L had the microstructural morphology of primary austenite with secondary δ-ferrite solidification mode, while the morphology of a δ-ferrite single phase solidification mode was observed within the unmixed zone that flowed out from the S32750. Furthermore, it could be speculated that each unmixed zone that flowed out from 316L and S32750 coexisted independently in terms of crystallographic aspect (orientation distribution function and predominant orientation relationship) analysed by electron backscatter diffraction.